Systems and Software Interface Survey. Issue 1 (30th September 2020) - Muscarella, Sally; Osaisai, Macaulay; Sheard, Sarah
Abstract: INCOSE formed the Systems and Software Interface Working Group (SaSIWG) in 2017, in response to Corporate Advisory Board interest in software, and problems identified in the systems and software interface (physical, logical, data and human). This third SaSIWG paper presents the results of a survey of systems engineers, software engineers, and project managers as to what are best practices and what are the priority challenges related to the interface between systems and software. The best practices mentioned by the 31 interviewees are grouped and summarized, followed by information on priority challenges and problems. Systems engineering must be done well, and that includes an ever‐increasing amount of Model‐Based Systems Engineering. It also includes developing and holding to a vision, addressing data, ensuring interdisciplinary work, planning systematic verification, and ensuring modularity. Systems Engineering must evolve to meet new challenges and most important, the expertise of systems engineers must include software engineering.